Pelatihan Keterampilan Tata Boga dan Manajemen Usaha untuk Peningkatan Ekonomi Keluarga di Desa Sanrobone, Takalar - Dahniyar Daud; Nuramal Nuramal; Rezki Arianty Akob; Andi Agus; Sitti Mispa; Susiana Mochtar; Gunawan. L. Pongkapadang (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2025)
This community service activity aims to improve culinary skills and micro-business management for the people of Sanrobone Village, Takalar Regency as an effort to increase family income and economic independence. The method of implementing the activity includes identifying needs, local ingredient-based culinary training, food sanitation workshops, micro-business management training, digital marketing, business plan preparation, and evaluation of results. The results of the activity showed a significant increase in processed food production skills, understanding of the importance of sanitation and food safety, and the ability to manage small-scale businesses. Participants were also able to utilize social media for product promotion and began designing home businesses independently or in groups. The formation of two joint business groups (KUB) is an indication that this training has fostered entrepreneurial initiatives among the village community. This activity is expected to contribute to strengthening the local economy in a sustainable manner and can be replicated in other villages with similar characteristics.